Effect of radioactive iodine therapy on hematological parameters in patients with thyroid cancer: systematic review and meta-analysis - Berta, Dereje Mengesha; Teketelew, Bisrat Birke; Cherie, Negesse; Tamir, Mebratu; Abriham, Zufan Yiheyis; Ayele Angelo, Abiy; Tarekegne, Amare Mekuanint; Chane, Elias; Mulatie, Zewudu; Walle, Muluken (Frontiers in Endocrinology, 2025)
BackgroundPatients with thyroid cancer (TC) are commonly treated with radioactive iodine therapy (RIA) to prevent neoplastic transformation and the re-emergence of cancer cells. However, it has major side effects on blood cells. However, the degree of change in hematological parameters reported varies across studies. Therefore, the aim of this review was to assesses the mean differences in hematological parameters after RAI therapy.MethodsThe relevant articles for this review were identified through extensive searches of databases and the Google search engine. The identified articles were subsequently selected using predetermined eligibility criteria. All relevant information from the screened articles was extracted. The pooled standardized mean differences (SMDs) of the parameters were assessed via a random effects model. The heterogeneity was determined by I2 statistics test. Funnel plots and Egger’s test were utilized to assess publication bias.ResultsA total of 17 studies including 4,112 and 3,766 study participants before and after RAI therapy, respectively, were included. The pooled SMDs of the total leucocyte count (TLC) (*109/L) at one, three, six and 12 months and the last follow-up period were 2.39, 2.46, 5.84, 3.19, and 0.53, respectively. Changes in the TLC after one, three and six months of therapy were statistically significant. In terms of the absolute neutrophil count (ANC; *109/L) and absolute lymphocyte count (ALC; *109/L), the pooled SMDs at the last follow-up period were 6.32 and 7.37, respectively. In addition, statistically significant changes in the platelet count (PLT; *109/L) were observed at one, three, six and 12 months and at the last follow-up, with pooled SMDs of 7.01, 0.22, 2.63, 6.61, and 8.76, respectively. Furthermore, statistically significant changes in red blood cells (RBCs; *1012/L) and hemoglobin (Hgb; g/dl) were detected after three and six months of therapy, with pooled SMDs of -1.088 and 2.4, respectively.ConclusionAccording to the current systematic review and meta-analysis, radioiodine therapy had a significant effect on hematological parameters. Thus, early screening and correction of hematological toxicity may be helpful for improving quality of life in thyroid cancer patients receiving radioiodine therapy.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024586449.